Ethical Commerce in the 21st Century: An Analytical Study of Islamic Business Ethics in Global and Digital Markets - Sihombing, Veronika Dinar Romauli; Sikki, Nurhaeni; Avrilya, Reghita; Maulida, Vida Wahda; Suri, Brigita Sheren Jesicca; Muhtar, Muhammad Hasan Zas (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This research explores the contemporary relevance of Islamic Business Ethics in addressing ethical challenges within globalized and digital markets in the 21st century. As business environments evolve through rapid technological advancement, including digital transformation, e-commerce, and artificial intelligence, Islamic ethical frameworks such as adl (justice), amanah (trustworthiness), ihsan (excellence), and shafafiyah (transparency) remain vital to ensure fairness, sustainability, and moral integrity in transactions. This paper adopts a qualitative descriptive-analytical approach, integrating literature review and case study analysis to identify the interconnection between traditional Sharia principles and modern business ethics standards such as Corporate Social Responsibility (CSR) and Environmental, Social, and Governance (ESG) principles. Findings indicate that Islamic ethics not only serve as moral guidance but also function as a competitive advantage in building consumer trust and ensuring sustainable growth in global commerce. The study emphasizes the potential synergy between Islamic moral codes and technological innovation, promoting ethical digital entrepreneurship, halal certification transparency, and fairness in financial transactions. By highlighting real-world applications in Islamic finance, halal industries, and digital trade ecosystems, this paper concludes that adherence to Islamic business ethics enhances global business resilience while aligning with universal ethical standards for responsible and sustainable commerce